WHY BOTHER WITH OUTSOURCING? - SUCCESS FACTORS AND CORE COMPETENCIES - Boone, Nicholas (Production Engineering and Management. Proceedings 4th International Conference. 25.- 26.09.2014 in Lemgo)
Outsourcing of logistics services is common practice for many manufacturers and retail companies. The main reasons given by decision makers are improving 'value for money' and flexibility. Often, this is justified with the company's need to focus on so-called 'core competencies'. Correspondingly, most outsourcing projects are triggered by the objective to reduce costs, while only a smaller proportion is driven by the objective to improve quality and overall performance. In reality, however, the expected benefits are often not (fully) achieved.